Erythrocyte sodium fluxes; intracellular . magnesium calcium and serum electrolytes in diabetes with pregnancy induce: hyi3ertension - Larmie, E.T. (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 1995)
Serum concentrations of sodium, potassium, ionised calcium, toted calcium, magnesium and erythrocyte sodium efflux rate constants were deternuned I spectrophotometricall~ and With 22 Na respectively in normotensive pre~nant i women (NP), normotersive pregnant womeh With diabetes m~llitus (Ofj), wotnen with diabetes msllitys and ~regn~ncy-itlduced hypertehsioh (DP-f:'IH) and women With pregnane 'nduc~J hyp~rtensioh (Nf:»-PIH) ~uring the third trimester I ' of pregnancy. No sig ificant diheten¢es were evident In: serum total rrlE:t~nesium I ' I sodium, potassium, a d lot1ised calci~m or ~rythrocyte hlagtiesium bstween the four groups. Serum t~tf=!l calcium, hbWSver, was Significantly (p<0.05) lower in NP-PIH women and ~tH women with diabetes mellitus. The cause for the lower serum total calcium iJ diabetic ahd hor1-diab9tic PIH women is hot evident but appears independent ~t the diabetes. I ! Erythrocyte mean total• sodium efflUx tate constant was significantly (p < 0.01) I higher in NP-PIH women. However, the mean ouabain-Insensitive sodium efflux rate constant was sligHtly higher in OP women. When compared to the other three groups. Mean ouabain-sensitive sodium efflux rate constant Was significantly (fl< 0.01; P < 0.05) higher in NP-fJIH and DP-PIH respectively. It would appear that while pre9nar1cy-induced hypertension increases the Na+, K+ -AT pase pump activity, this effect is moderated In the presence of a preexistin9 diabetes niellitus.